(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The term “mercantilism” was introduced into scientific circulation by French Enlightenment philosophers. In economic science, it is used, firstly, to determine the historical period within which the decomposition of the natural economy and the formation of a system of market relations took place.